Ethnography as the tool to understand space and place / Mohd Iqbal Hashim - Hashim, Mohd Iqbal (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
As we traverse the street through Kampung Gersik to Kampung Bintawa, at first glance, we see that the redevelopment of the whole area is underway. If we carefully make our way from Kampung Boyan, we will first encounter a lively arterial public space dotted with diverse small enterprises. Then, we succeedingly encounter houses built too near the street that their threshold fleets by. Only when we observe carefully can we make out its character. Passing through them deep enough, we start to feel that the urban scale – exacerbated by the towering masses over the Tebingan Sarawak – is slowly being brought down to a more human scale and sympathetically articulated street.